STUDI TENTANG ANAK HIPERAKTIF PADA PESERTA DIDIK KELAS 5 DI SD NEGERI 52 PONTIANAK TAHUN 2022 - Aziz, Irfan Abdul; Wicaksono, Luhur; Fergina, Ana (Universitas Tanjungpura, 2023)
The purpose of this study was to identify and describe hyperactive students in grade 5 at SD Negeri 52 Pontianak. Hyperactive children are an increase in children's motor activity to a certain level and cause behavioral disturbances that occur in two different places and situations. The subjects in this study were three students. Thisresearch is an intrinsic case study research. Data were colleced by in-depth interviews, observation and documentation. Data was analyzed by an interactive model consisting of data reduction, data presentation and conclusion. The research findings shaved that, the characteristics of hyperactive children are seen from their characteristics. namely hyperactivity, excessive activity, disturbed feeling of confusion, impulsivity and exitability. Factors causing students to become hyperactive are parenting styles and the environment. there factors impact students social interaction in school environment, friendship, problem solving and decreased academic grades. The teacher's role in guiding hyperactive children is to monitor student development by working closely with teachers in other fields of study, classroom teachers and parents.